A Design Method of Harmonic Mixers Based on Schottky Diodes Applied for Millimeter Wave Components. Issue 3 (27th March 2022) - Jiang, Yiyi; Gu, Xiya; Cui, Can
Abstract: On the basic theory of millimeter wave mixing technology, harmonic mixers in multiple different frequency bands are systematically studied. This paper innovatively establishes a 3D model of the diode, gives it material properties, and uses magnetic field circuit software for co‐simulation, and finally develops a beautifully structured W‐band 89 GHz sub‐harmonic mixer. Simulation and test results show that when the local oscillator (LO) is fixed at 45 GHz, the conversion loss of the LO at 84–94 GHz is better than 14 dB, and the minimum conversion loss is 9 dB. The actual test results are relatively consistent with the simulation trend. Plain Language Summary: In this paper, a design method of harmonic mixer is studied, and the correctness of the method and the accuracy of the model are verified by experimental results. Key Points: This paper systematically studies mixers in several different frequency bands. Starting from the study of the internal structure and material size package of Schottky planar diodes, some new modeling ideas were proposed A simulation method of field‐to‐path combination is proposed, and the transition circuit and the resonance matching circuit are analyzed The designed harmonic mixer is tested and analyzed, which fully verifies the accuracy of the diode 3D electromagnetic model and the rationality of the simulation method